Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1007/bf02678146
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro andIn Vivo induction of bone formation using a recombinant adenoviral vector carrying the human BMP-2 gene

Abstract: It has been well established that bone morphogenetic protein-2 (BMP-2) can induce bone formation both in vivo and in vitro, although high concentrations (up to milligrams) of BMP-2 have been required to achieve this effect in vivo. Further, clinical applications are usually limited to a single dose at the time of implantation. In an attempt to prolong the transforming effect of BMP-2 we used a recombinant adenoviral vector carrying the human BMP-2 gene (Adv-BMP2) to transduce marrow-derived mesenchymal stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 19 publications
5
86
1
1
Order By: Relevance
“…[16][17][18] Similar to the results in NIH-3T3 and MC3T3-E1 cells, gene transfer of both AdBMP-2 and AdLMP-3 induced bone mineralization in hMSCs, as confirmed by the Von Kossa staining ( Figure 5). …”
Section: Control Adψ5supporting
confidence: 79%
“…[16][17][18] Similar to the results in NIH-3T3 and MC3T3-E1 cells, gene transfer of both AdBMP-2 and AdLMP-3 induced bone mineralization in hMSCs, as confirmed by the Von Kossa staining ( Figure 5). …”
Section: Control Adψ5supporting
confidence: 79%
“…In most of these studies bone healing could be achieved with a single-dose administration of rhBMP-2. [6][7][8][9][10]14,29,32 Sellers et al 33 reported a mean residence time of rhBMP-2 of 8 days with an elimination half-life of 5.6 days in a cartilage defect model. Explanations for the successful repair of bone defects by a protein that is only present for a few days may be the initiation of differentiation cascades or the recruitment of a sufficient number of the required cells already within the first days.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Although encouraging results were achieved with this and other recombinant BMPs, two of which have already successfully traversed clinical trials, several obstacles still have to be overcome. The production of rhBMPs is very expensive, and successful bone healing requires high amounts of protein, 9 which might spread throughout the patient's body with inadvertent accumulation in nontarget organs. Regional gene transfer may therefore provide a viable alternative to protein therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Past work in our laboratory has shown that we can transfer the gene for bone morphogenetic protein 2, (BMP-2) a growth factor for bone cells, into bone marrow MSC and mesenchymal progenitor cells via recombinant adenovirus. These geneengineered cells continuously expressed BMP-2 protein both in vitro and in vivo, and facilitate cell differentiation into cells of the osteoblast lineage by both autocrine and paracrine [28,40,44].…”
Section: H T W~h I D U Et Ui I Journul Of Ortliopuedicmentioning
confidence: 99%